2022
DOI: 10.1177/13591053221084858
|View full text |Cite
|
Sign up to set email alerts
|

Psychological homeostasis and protective behaviours in the COVID-19 pandemic

Abstract: Since the first case of human SARS-CoV-2 infection late in 2019 workers across multiple disciplines have been strenuously engaged in attempting to prevent the spread of the virus and to provide care to patients. Never in history has so much human effort been concentrated on a single health trauma. Much of the new research is empirical in nature with relatively few strands of theory. This article focuses on two recent theories relevant to COVID-19 protective behaviours, the COM-B and the General Theory of Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
(68 reference statements)
0
5
0
1
Order By: Relevance
“…Furthermore, knowledge has been extensively thought of as a critical component in the fight against COVID‐19, 37 as individuals with high levels of knowledge are more likely to have protective motivation. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, knowledge has been extensively thought of as a critical component in the fight against COVID‐19, 37 as individuals with high levels of knowledge are more likely to have protective motivation. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, this study demonstrated that educational level, which is generally considered related to knowledge, is an influential factor in the intention. Furthermore, knowledge has been extensively thought of as a critical component in the fight against COVID‐19, 37 as individuals with high levels of knowledge are more likely to have protective motivation 38,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The General Theory of Behaviour suggests that 'human thriving is dependent upon an intrinsic homeostasis system with purpose, desire and intentionality striving to maintain equilibrium'. 47 Figure 1 of a recent paper 48 illustrates how psychological homeostasis might be maintained in response to change through a behavioural homeostatic process, the reset equilibrium function. 37 The biopsychosocial model of illness suggests that a person will balance physiological (i.e., biological), psychological, and social parameters.…”
Section: Biopsychosocial Adaptationmentioning
confidence: 99%
“…Having brought great uncertainty to multiple aspects of our lives, it affects our mental health, education and work, for we are unsure when the pandemic will end. Therefore, in the post-COVID-19 era, scientists have unanimously scrambled to research how the pandemic can be effectively treated while also showing concern about its impact on our mental health and career development ( Cunningham et al, 2020 ; Marks, 2022 ). To date, studies on individual career development in the context of the COVID-19 global pandemic have focused on health care workers, medical students, and nursing students (e.g.…”
Section: Introductionmentioning
confidence: 99%